Causes And Problems Of Population Displacement Of The Mishings Of Dhemaji Due To Flood Vulnerability - Raju Pegu, Likhan Ch. Doley, (International Journal of Scientific Research and Management (IJSRM), 2015)
The Government has identified Dhemaji district as the most backward and poorest district in the State, mainly due to thefact that most portion of the area is affected by yearly floods. The population inhabited by different people groups such asMishing, Bodos, Deories, Assamese, Adivasi, Muslim and various non tribal groups. The total current population ofDhemaji is 688077.The male & female population showcasing 353043 and 335034 respectively. The Mishingcommunity constitutes the largest population of the area. The Mishing people are active agriculturists. Their mainoccupation for livelihood is agriculture. In the past, they had a practice of shifting cultivation in the hills but after settlingdown in the plains, they are now practicing settled cultivation. The literacy rate of the Mishing people is poor. The Stateliteracy rate has gone up to 73% percent whereas the Mising literacy rate is at 45% in the district. This is due to a lack ofproper educational institutions, a lack of awareness and also due to the yearly flood disaster in the district. Education hasbeen given very little priority. The health status of the people is very poor. Water-borne diseases in the area are rampantdue to floods and stagnant water after the disasters. The yearly flood have been destroying their cultivable land by soilerosion or by sand deposition, damaging educational institutions, washing away their properties that is private property aswell as public property and even sometimes taking away peoples life. The frequent flood disasters in the area have beenincreasing the percentage of BPL card holders yearly. Aftermath of flood disaster this particular tribe lack rehabilitationtribulations due to various factors. It has been observed that their simple way of settlement pattern has been affected byflood resulting displacement of households to elsewhere. In the recent year we have been seen that a new trend ofsettlement pattern that is settlement in the broken embankments or high platforms or highland areas. Therefore, in orderto analysis the actual facts within the districts a case study were conducted in the Machakhowa Dev. Block andSissiborgaon Dev. Block. The research paper is entitled as “Causes and Problems of Population Displacement ofthe Mishings of Dhemaji due to Impact of Flood Vulnerability”.